Evaluation of silicon based microdosimetry for Boron Neutron Capture Therapy Quality Assurance. (October 2019) - Vohradsky, James; Guatelli, Susanna; Davis, Jeremy A.; Tran, Linh T.; Rosenfeld, Anatoly B.
Highlights: Characterisation of a novel Bridge Microdosimeter by means of Geant4 in BNCT. The microdosimeter does not pose radiation protection risks in terms of activation. Recommendations are provided to improve the design of the device. Abstract: The shift from reactor to accelerator based neutron production has created a renewed interested in Boron Neutron Capture Therapy (BNCT). BNCT is reliant upon the favourable uptake of 10 B by tumour cells along with the interaction with neutrons to produce high LET fragments (He and Li nuclei) that deposit energy locally within the tumour cells. As with any radiation based treatment, Quality Assurance (QA) is crucial. In particular, Geant4 was used to model and optimise the geometry and packaging of Silicon on Insulator (SOI) microdosimeters for BNCT Quality Assurance purposes in view of experimental measurements at the KUR research reactor, in Japan. In this context, design optimisation pertains to the sensitive volume size and probability of neutron activation. This study has shown conclusively that whilst the materials currently used in the fabrication of silicon based microdosimeters are appropriate, there are changes with respect to the sensitive volume thickness that should be addressed to reduce the number of 'stoppers' in the microdosimeter.